Sintering behavior, microwave dielectric properties, and chemical bond features of novel low-loss monoclinic-structure Ni3(PO4)2 ceramic based on NiO-P2O5 binary phase diagram. Issue 20 (15th October 2022) - Feng, Zhanbai; Wang, Yingzi; Kimura, Hideo; Li, Xianglong; Zhang, Yanbin; Zhang, Yuping; Du, Jialun; Yu, Xuan; Teng, Xinying; Wu, Haitao
Abstract: Ni3 (PO4 )2 as microwave dielectrics was investigated in terms of sintering behavior and microwave dielectric properties and synthesized using the solid-state sintering method. X-ray diffraction (XRD) data revealed that the Ni3 (PO4 )2 ceramics belong to the monoclinic structure with the P21 /c (#14) space group. The sintering behavior analysis confirmed that the sample reached a dense state at 1200 °C. It's permittivity ( ε r ) and quality factor ( Q × f ) possess distinct density-dependent features. The admirable Q × f of 83, 430 GHz (at 10.21 GHz) was accomplished coupled with a low ε r of 6.23 and temperature coefficient of resonant frequency ( τ f ) of −24.63 ppm/°C in Ni3 (PO4 )2 ceramic when sintering at 1200 °C for 2 h. Thus, it is a promising candidate for microwave dielectrics with low loss and low permittivity. The dielectric properties were discussed using the chemical bond theory, and their chemical bond features were quantified. The results confirmed the significance of P–O bonds in the microwave dielectric response of Ni3 (PO4 )2 ceramic.